P3_2 Railguns! Miniaturised? - Smith, Kennedy; Bates, Ethan; Brewer, Lois; Sadler, Tommy (Physics Special Topics, 2022)
Rail-guns (RG) are theorised to be the weapons of the future, with the ability to propel ordinance at large velocities in excess of ∼ 2kms−1 [1]. We are investigating whether this technology can be miniaturised into mobile soldier equipment. We find that these weapons could be miniaturised to ∼ 700mm barrel length, however there is currently no power source small and powerful enough to be deployed in this manner.